Effectiveness of Emotionally-Focused Couples Therapy on Marital Violence, Marital Adjustment, and Sexual Intimacy of Couples Visiting Counseling Centers of Ahvaz - Panabad, Simin; Gholamzadeh Jofreh, Maryam; Asgari, Parviz; Kazemian Moghaddam, Kobra (Advances in Nursing & Midwifery, 2022)
Introduction: Successful sexual relationships and intimacy would improve marital adjustment in couples, acting as a significant predictor of marital satisfaction. The present study aimed to investigate the effectiveness of emotionally-focused couples therapy (EFCT) on marital violence, marital adjustment, and sexual intimacy of couples visiting counseling centers of Ahvaz. Methods: This study adopted a single-case research design with the noncurrent multiple baseline approach. The statistical population included all the volunteer couples with lack of marital adjustment visiting the counseling centers of Ahvaz, Khuzestan Province (Iran) in 2021. Purposive sampling was employed to select two couples (i.e., four individuals). The therapy protocols were administered to all participants in two phases: an 18-session intervention and four baseline steps including a first 45-day follow-up and a later 3-month follow-up. Research questions were employed to analyze the participants before the therapy in sessions 4, 8, 12, 16, and 18 as well as the 45-day and 3-month follow-ups. The Dyadic Adjustment Scale (DAS), Couples' Sexual Intimacy Questionnaire and the Violence Against Women Questionnaire were used to collect data. The visual analysis method, the reliable change index (RCI), and the recovery percentage formula were used for data analysis. Results: According to the results, the EFCT managed to significantly improve sexual intimacy, mitigate marital violence, and improve poor marital adjustment among participants at the end of the therapy and during the 45-day and 3-month follow-ups. Conclusions: This study achieved promising results concerning the applicability of EFCT. Hence, the EFCT can alleviate both marital violence and poor marital adjustment in addition to enhancing sexual intimacy among couples.